The Role of the Police Civil Servant Unit in Handling LGBT Cases in Bukittinggi City - Yusra Dila Maiza; Riki Zulfiko (DE'RECHTSSTAAT, 2025)
Bukittinggi as a tourist city is inseparable from a social phenomenon, one of the phenomena is LGBT, according to the philosophy of "Adat basandi syarak, syarak basandi kitabullah" states that LGBT does not exist in culture, custom and religion. This research aims to find out how the role of Satpol PP and identify obstacles in handling LGBT cases in Bukittinggi City. The formulation of this problem aims to examine the functions of Satpol PP and the challenges faced by Satpol PP related to LGBT cases in Bukittinggi City. Descriptive in nature, this research falls into the category of empirical legal research. Based on the results of the research, Satpol PP uses preventive and repressive measures when dealing with LGBT. Preventive efforts are in the form of socialization about the dangers and impacts of LGBT, repressive efforts by way of after a report or caught red-handed, arrest by URC, making an incident report, incident reports and evidence are submitted and registered to the PPUD field to the PPNS section, examination, making BAP and given sanctions. The obstacles faced in LGBT prevention are the lack of public knowledge about LGBT and the lack of public participation by not reporting LGBT, repressively are the perpetrators who are less cooperative, the difficulty of distinguishing perpetrators from normal people, the absence of laws on LGBT and the absence of rehabilitation centers for LGBT.